2022
DOI: 10.1002/brb3.2648
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the link between cognitive deficit, self‐esteem, alexithymia, and depressive symptom of schizophrenia

Abstract: Objective: To the best of our knowledge, studies have been rarely conducted to assess the correlation between cognitive deficit, self-esteem, and alexithymia in the depressive symptoms of schizophrenia (SCZ). Therefore, this study aims to explore the risk factors associated with impairment of cognitive function, alexithymia, and self-esteem among a representative sample of first-episode schizophrenic patients. Method:We recruited 107 first-episode schizophrenic patients (48.6% male, 51.4% female, 36.94 ± 10.73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
2
8
0
Order By: Relevance
“…Consistent with prior studies (Fogley et al, 2014; He et al, 2022), we found that patients with alexithymia had significantly poorer neurocognition. There are several possible explanations.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with prior studies (Fogley et al, 2014; He et al, 2022), we found that patients with alexithymia had significantly poorer neurocognition. There are several possible explanations.…”
Section: Discussionsupporting
confidence: 92%
“…This study demonstrated a strong association between alexithymia and clinical symptoms in patients with schizophrenia. Notably, negative symptoms were independently associated with alexithymia, which supports previous findings (He et al, 2022; Yi et al, 2022). Interestingly, our results indicated that patients with alexithymia did not exhibit higher depressive symptoms.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“… 60 However, the relationship has not been examined in the adolescent group. Besides, Dong et al’s research 61 has demonstrated that self-esteem mediates the association between alexithymia and NSSI, that is, individuals with alexithymia may have a higher risk of experiencing a sense of low self-esteem, 62 which may lead to NSSI behaviors. Therefore, we hypothesized that the influence of bullying victimization on NSSI is mediated by the chain mediating role of alexithymia and self-esteem (Hypothesis 4).…”
Section: Introductionmentioning
confidence: 99%